Bael to make socio-economically empowered - Dutt, Som (Indian Horticulture, 2019)
The bael, hitherto a very lesser-known fruit plant but with a huge socioeconomic potential, has not been given importance it deserves. To tap its tremendours potential, a number of institutions started to do research on bael. Of them, our Central Horticultural Experiment Station (CHES), Godhra, of the Central Institute for Arid Horticulture, Bikner, has come up with the development of a number of commercial varieties and technologies which are very popular among farmers. To showcase them, a bael day was celebrated on 4 May 2015, at CHES, Godhra. There was an excellent response among bael growers, farmers, entrepreneurs and other stakeholders. Varietal wealth, varied germplasm and technologies were exhibited to all visitors. Since scientists of CHES, Godhra, have done a commendable job in development of commercial varieties, collection of valued germplasm, technology development and popularization of bael at the grassroot level, this Centre needs to be upgraded as the centre for Excellence on Bael.